2014
DOI: 10.1007/s00410-014-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

Origin of sub-lithospheric diamonds from the Juina-5 kimberlite (Brazil): constraints from carbon isotopes and inclusion compositions

Abstract: interpreted as evidence of diamond growth from abiotic organic carbon added to the oceanic crust during hydrothermal alteration. The bulk isotopic composition of the oceanic crust, carbonates plus organics, is equal to the composition of mantle carbon (−5 ‰), and we suggest that recycling/mixing of subducted material will replenish this reservoir over geological time. Several exposed, syngenetic inclusions have bulk compositions consistent with former eclogitic magnesium silicate perovskite, calcium silicate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
82
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 117 publications
(184 reference statements)
9
82
0
2
Order By: Relevance
“…All lines of evidence point to a related, sub-lithospheric, origin for the diamonds studied. The diamonds have δ 13 C values from -26.4 ± 0.1 to -2.8 ± 0.1 ‰ and all measurements are consistent with previously published data for these and other samples from the same localities , Thomson et al, 2014. Mineral inclusion δ 18 O values range from 7.5 ± 0.3 to 12.9 ± 0.3 ‰ and are anticorrelated with δ 13 C of the host diamonds (Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…All lines of evidence point to a related, sub-lithospheric, origin for the diamonds studied. The diamonds have δ 13 C values from -26.4 ± 0.1 to -2.8 ± 0.1 ‰ and all measurements are consistent with previously published data for these and other samples from the same localities , Thomson et al, 2014. Mineral inclusion δ 18 O values range from 7.5 ± 0.3 to 12.9 ± 0.3 ‰ and are anticorrelated with δ 13 C of the host diamonds (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Our model is also compatible with all other observations of melting of carbonated subducted crust and the mineralogy and compositions of inclusions in superdeep diamonds, including the scarcity of carbide and metal (Bulanova et al 2010, Thomson et al 2014). Moreover, a study of the coupled behaviour of C and N isotopes in Juina diamonds similarly found evidence for a mixing relationship between crustal and mantle components (Palot et al, 2012).…”
supporting
confidence: 76%
See 3 more Smart Citations